Development of esophagogastroduodenoscopy in China: results from the national census in 2013 and 2020 - Zhou, Siwei; Chen, Zheran; Jiao, Yunfei; Cheng, Zhiyuan; Gao, Ye; Wang, Tianjiao; Xin, Lei; Wan, Rong; Wang, Luowei (Frontiers in Oncology, 2024)
Given the significant burden of upper digestive diseases, there has been a substantial increase in the utilization of esophagogastroduodenoscopy (EGD) in China from 2012 to 2019. The objective of this study is to investigate the development, practice, and factors influencing the widespread use of EGD during this period.: Two national censuses were conducted among all hospitals in mainland China that perform gastrointestinal endoscopy. These censuses aimed to extract information on the infrastructure, volume, and quality of EGD. The analysis of potential factors influencing EGD practice was based on real-world data from open access sources.From 2012 to 2019, the number of hospitals performing EGD in mainland China increased from 1,518 to 2,265 (1.49-fold) in tertiary hospitals and from 3,633 to 4,097 (1.12-fold) in secondary hospitals, respectively. The national utilization rate of EGD also increased from 1,643.53 to 2,018.06 per 100,000 inhabitants, indicating a 1.28-fold increase. Regions with more endoscopists per 100,000 inhabitants (OR 9.61, P<0.001), more tertiary hospitals performing EGD per million inhabitants (OR 2.43, P<0.001), higher incidence of esophageal and gastric cancer (OR 2.09, P=0 016), and higher number of hospitals performing EGD per million inhabitants (OR 1.77, P=0.01) tended to provided more numerous and qualitied EGD. And hospital grading, regional GDP, incidence of esophageal and gastric cancer and the volume of EGD were observed as the significantly relevant factors of malignant dictation rate (MDR) (P<0.05), but not the number and educational background of endoscopists.Over the past seven years, China has made significant progress in EGD. However, challenges persist in terms of quality and inequality.